2017
DOI: 10.1016/j.lcsi.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Transitions as sites of socialization in family interaction outdoors

Abstract: In this study, we explore transitions in social interaction as sites for socialization: we discuss the significance of transitions for how participants establish an appropriate orientation to an activity, provide each other opportunities to participate in the activity and make the social order of the activity visible. We draw on ethnomethodological conversation analysis and video recordings in English and Finnish in which families with children engage in the activity of foraging, i.e. picking wild produce.We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 39 publications
1
9
0
2
Order By: Relevance
“…For example, social learning theory views vicarious (observational) learning as copying or imitating the behaviours of others within a social and cultural context (Marsick, 2009; Aoki and Feldman, 2014) whereas the theory of informal and incidental learning considers vicarious learning to be learning ‘en passant’, in a context with triggers for learning, resources and environmental influences (Marsick, 2009; Boekaerts and Minnaert, 1999). In addition, socialisation theory defines vicarious learning as learning through practices and social actions (Keisanen et al, 2017; Forrester, 2013; Keel, 2016; Gottfredson, 2002). These theories and their concepts of vicarious learning have evolved over time and are used in different contexts, for instance, in studies on the role of informal learning in formal education.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…For example, social learning theory views vicarious (observational) learning as copying or imitating the behaviours of others within a social and cultural context (Marsick, 2009; Aoki and Feldman, 2014) whereas the theory of informal and incidental learning considers vicarious learning to be learning ‘en passant’, in a context with triggers for learning, resources and environmental influences (Marsick, 2009; Boekaerts and Minnaert, 1999). In addition, socialisation theory defines vicarious learning as learning through practices and social actions (Keisanen et al, 2017; Forrester, 2013; Keel, 2016; Gottfredson, 2002). These theories and their concepts of vicarious learning have evolved over time and are used in different contexts, for instance, in studies on the role of informal learning in formal education.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…This study showed that nature truly is an important aspect in families' lives, suggesting that parents who value nature might have better relationships with their children as a result. The results of this study also suggest the important role that parents play in socializing their children to the outdoors, as previously demonstrated by Mayer et al (2009) and Keisanen, Rauniomaa, and Siitonen (2017), supporting the present study's finding that parents' nature connectedness was associated with child nature connectedness.…”
Section: Strengths Limitations and Future Directionssupporting
confidence: 91%
“…It has long been understood that contact with nature has beneficial components for overall well-being (Wilson, 1984) as well as for relationship interactions (Keisanen, Rauniomaa, & Siitonen, 2017); however, research has yet to encompass just how grand of a role the great outdoors has in developing children and family life. Contact with nature is suggestive of nature connectedness, which is viewed as the strong affinity towards and emotional connection with nature that many experience (Wilson, 1984).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Luontoiluaineistossamme osallistujat liikkuvat tilassa, käsittelevät objekteja ja ohjaavat toisiaan ottamaan haltuun luontoilutoiminnalle ominaisia kehollisia käytänteitä, esimerkiksi poimimaan kaikki käden ulottuvilla olevat marjat samalla kertaa (ks. Keisanen, Rauniomaa & Siitonen 2017). Toiminta rakentuu siis pitkälti kehollisuuden, tilan ja liikkeen ehdoilla, ja tämä näkyy myös multimodaalisten toimintojen muotoilussa ja tulkinnassa.…”
Section: Kato Multimodaalisen Vuorovaikutuksen Resurssinaunclassified